Degradation of oxygen reduction reaction kinetics in porous La0.6Sr0.4Co0.2Fe0.8O3-δ cathodes due to aging-induced changes in surface chemistry - Baque, Laura Cecilia (2017)
The modification of surface composition after long-term operation is one of the most reported degradation mechanisms of (La,Sr)(Co,Fe)O3-δ (LSCFO) cathodes for Solid Oxide Fuel Cells (SOFCs). Nevertheless, its effect on the oxygen reduction reaction kinetics of porous LSCFO cathodes has not been yet reliably established. In this work, La- and Sr-enrichment at the LSCFO surface of porous cathodes has been induced after 50 h aging at 800 °C under air. Such cation redistribution can extend up to ∼400 nm depth under the LSCFO surface as detected by high resolution Scanning Transmission Electron Microscopy-Energy Dispersive Spectroscopy maps acquired inside the cathode pores. The observed surface chemical changes hamper the oxygen surface exchange reaction at the LSCFO/gas interface. Accordingly, a suitable Electrochemical Impedance Spectroscopy analysis revealed that the oxygen ion conductivity remains practically unaltered during the aging treatment while the oxygen surface exchange resistance increases up to 1.8 times. As a result, the cathode impedance response deteriorates within the 10–0.1 Hz frequency range during the aging treatment, resulting in a total cathode area specific resistance increase of 150%. The methodology adopted has demonstrated to be very valuable for studying the degradation of SOFC cathodes produced by the modification of surface composition.